THE FAMILIARITY OF THE PRE-SERVICE ENGLISH TEACHERS WITH THE HIGHER ORDER THINKING SKILLS IN ELT - Muh. Basuni (Jurnal Bahasa Lingua Scientia, 2019)
Since higher order thinking skills have been targeted as one of the instructional objectives at Indonesian schools, investigating to what extent the pre-service English teachers are familiar with the concept of the higher order thinking skills in ELT is necessary. The current study was conducted to investigate to what extent the pre-service English teachers are familiar with the concept of higher order thinking skills in English language teaching. A survey research was employed which encompass 109 respondents. The finding of the current study reveals that the familiarity of the pre-service English teachers with the concepts of the higher order thinking skills in ELT is at the moderate level. It indicates that most pre-service English teachers are quite familiar with the concept of the higher order thinking skills but their knowledge is not deep. The implication to the teaching of English language may be that the teaching of the higher order thinking skills are not fully infused to the English language teaching. Therefore, future researchers are recommended to investigate the English teachers’ practice dealing with the promotion of the higher order thinking skills.